Solve for g g(-3)=-3-1

Math
g(-3)=-3-1
Subtract 1 from -3.
g(-3)=-4
Divide each term by -3 and simplify.
Tap for more steps…
Divide each term in g(-3)=-4 by -3.
g(-3)-3=-4-3
Cancel the common factor of -3.
Tap for more steps…
Cancel the common factor.
g⋅-3-3=-4-3
Divide g by 1.
g=-4-3
g=-4-3
Dividing two negative values results in a positive value.
g=43
g=43
The result can be shown in multiple forms.
Exact Form:
g=43
Decimal Form:
g=1.3‾
Mixed Number Form:
g=113
Solve for g g(-3)=-3-1

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top